2019
DOI: 10.1039/c8fo01845f
|View full text |Cite
|
Sign up to set email alerts
|

Identification of α-glucosidase inhibitors fromcyclocarya paliurustea leaves using UF-UPLC-Q/TOF-MS/MS and molecular docking

Abstract: 11 potential α-glucosidase inhibitors in leaves of Cyclocarya paliurus were quickly identified by UF-UPLC-Q/TOF-MS/MS, and their inhibitory activities were verified in vitro and in vivo, as well as docked with homology model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 32 publications
3
40
0
Order By: Relevance
“…Extracts of Cyclocarya paliurus (CP) tea leaves inhibit α-glucosidase activity at an IC 50 value of 31.5 ± 1.05 μg/mL which is very much lower than the IC 50 value of 296.6 ± 1.06 μg/mL, i.e., of acarbose, the positive control ( Ning et al, 2019 ). The active components of the extract with α-glucosidase inhibitory activity were quercetin-3- O -glucuronide, quercetin, kaempferol-3- O -rhamnoside, kaempferol, genistein and asiatic acid [ Fig.…”
Section: Dietary Sources and Their Bioactive α-Glucosidase Inhibitorsmentioning
confidence: 95%
See 1 more Smart Citation
“…Extracts of Cyclocarya paliurus (CP) tea leaves inhibit α-glucosidase activity at an IC 50 value of 31.5 ± 1.05 μg/mL which is very much lower than the IC 50 value of 296.6 ± 1.06 μg/mL, i.e., of acarbose, the positive control ( Ning et al, 2019 ). The active components of the extract with α-glucosidase inhibitory activity were quercetin-3- O -glucuronide, quercetin, kaempferol-3- O -rhamnoside, kaempferol, genistein and asiatic acid [ Fig.…”
Section: Dietary Sources and Their Bioactive α-Glucosidase Inhibitorsmentioning
confidence: 95%
“…6 ]. Studies related to molecular docking have revealed that these components can occupy the active sites of α-glucosidase more easily than acarbose ( Ning et al, 2019 ).…”
Section: Dietary Sources and Their Bioactive α-Glucosidase Inhibitorsmentioning
confidence: 99%
“…Such values were similar as previous reports with the energy of À10.0 kcal mol À1 for quercetin or À9.3 kcal mol À1 for kaempferol binding to a-glucosidase. 49 Hydrogen bonds and Pi interactions were also formed between their interactions with the enzyme (Fig. 3B).…”
Section: Molecular Docking Analysismentioning
confidence: 95%
“…Cyclocarya paliurus , known as Qing-Qian-Liu due to the resemblance of its fruit clusters to a string of old Chinese copper coins, is a sole species in this genus [4]. Because of its diverse functions, C. paliurus has attracted a lot of attention [5,6,7]. However, the natural forest resources are mainly distributed in the mountain areas that are hard to reach or some nature reserves [8].…”
Section: Introductionmentioning
confidence: 99%